PEMANFAATAN GEOGEBRA UNTUK VISUALISASI GELOMBANG LISSAJOUS - Asbanu, Dens E. S. I. (Universitas Tadulako, 2021)
This study aims to study the visualization and GeoGebra operations for the simulation of Lissajous waves as a substitute for the oscilloscope screen. The research subject is GeoGebra software. This research was conducted at the STKIP SoE Science Laboratory. This research is expected to produce visualization and operating system of Lissajous waves on GeoGebra. The data used in this study are fixed amplitude, frequency ratio 1:1 with a phase difference of 00, 450, 900, 1800, 2700, 3600. Other data used is the ratio of frequency equal to amplitude = 2:5 at a phase difference of 900 and 1800. Comparison of the phase difference between 900 and 1800. frequency, amplitude, and phase difference are the main variables in the formation of Lissajous waves. It is concluded that GeoGebra software can be used for simulating Lissajous waves such as on an oscilloscope screen. This simulation media can be used by students and teachers in understanding Lissajous wave patterns.